ROLE OF PECTIC ENZYME IN THE ROTTING OF MANGO DEAD WOOD BY THE FUNGUS - CLITOCYBE MULTICEPS - BASUNDHARA TH,; G.A. SHANTIBALA, (The Bioscan, 2019)
Wood rotting is naturally caused by the action of insects, fungus, bacteria, nematodes, etc. Fungi produce many enzymes playing main role in the decaying of dead wood. To investigate the rotting action of enzymes produce by the fungus - Clytocybe multiceps, the fungus species was collected from various localities when they are grown vigorously during rainy season, brought to the lab for further study. The methodology adopted by Cole and Wood (1961) was followed. The study reveals the role of fungal enzymes in rotting of mango wood by the pectic enzyme produced by the fungus - Clitocybe multiceps. This fungus produce pectic enzyme which can degrade the layer of cell wall of host tissue leading to rotting. The stipe or stalk portion of the fungus is found to produce more amount of the wood - rotting pectic enzymes - polygalacturonase (PG), than the pileus portion. The cellulolytic enzymes - polygalacturonase and polymethylesterase (PME) were produced during pathogenesis of the wood rotting action of the dead tree wood by the fungus. The main aim of the present work is to investigate the role or action of pectic enzyme in the decay of dead mango wood tissue and is discussed.